Impact of improved groundnut (Arachis hypogaea L.) production technologies on knowledge and adoption of farmers: IMPACT OF GROUNDNUT PRODUCTION TECHNOLOGIES ON KNOWLEDGE AND ADOPTION OF FARMERS - N VENKATESHWAR RAO; P K JAIN; N KISHOR KUMAR; M JAGAN MOHAN REDDY (Journal of Oilseeds Research, 2016)
Groundnut is an important oilseed crop in Karimnagar district, Telangana state. The KVK, Karimnagar has disseminated improved groundnut production technologies to the farmers of the district through village adoption, technology assessment, refinement, demonstrations and farmer field schools. Further, the KVK has used various modes of communication such as electronic and print media for popularization of technologies. An impact assessment was done in 15 adopted villages with 60 farmers and 15 non-adopted villages with 30 farmers to assess the increase in knowledge and adoption of groundnut technologies. An Ex-post facto research designed was used for impact assessment. The results indicated significant differences in level of knowledge and extent of adoption between farmers of KVK-adopted villages and non-adopted villages. The knowledge scores were high in 48 per cent of farmers from adopted villages whereas high knowledge scores were observed in 23 per cent of farmers from non-adopted villages. The extent of adoption was high in 45 per cent of farmers from adopted villages, whereas it was 27 per cent from non-adopted villages. Farmers from adopted and non-adopted villages possessed knowledge of improved varieties such as K6 and application of gypsum. Deep ploughing and irrigating the crop at regular intervals were adopted by majority of the farmers in non-adopted villages.